2016
DOI: 10.15171/bi.2016.02
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of mesenchymal stem cell differentiation into the endoderm lineage by four step sequential method in biocompatible biomaterial

Abstract: Introduction: The goal of the study described here, was to investigate the potential of umbilical cord derived mesenchymal stem cell (UC-MSCs) into hepatocyte like cells in a sequential 2D and 3D differentiation protocols as alternative therapy. Methods: Mesenchymal stem cells (MSCs) were isolated from the umbilical cord (UC) and CD markers were analyzed by flow cytometry. For hepatic differentiation of UC-MSCs, cells were induced with a sequential 4-step protocol in 3D and 2D culture system. Urea concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Conversely, the high expression of both CDH1 and SOX7 in BM-MSCs (Fig. 5) may infer the existence of an endodermal precursor which is in line with the potential of these cells to transdifferentiate into endodermal lineages [50]. Overall, a similarly low level of MIXL1 detected on both cell types implies their…”
Section: Imscs Were Derived Through Mesodermal Commitmentmentioning
confidence: 82%
“…Conversely, the high expression of both CDH1 and SOX7 in BM-MSCs (Fig. 5) may infer the existence of an endodermal precursor which is in line with the potential of these cells to transdifferentiate into endodermal lineages [50]. Overall, a similarly low level of MIXL1 detected on both cell types implies their…”
Section: Imscs Were Derived Through Mesodermal Commitmentmentioning
confidence: 82%
“…Other studies reported that TSA may reverse the age impact within other human MSC subtypes and inhibits in-vitro differentiation of BMSCs into neuronal lineage cells [ 73 , 74 , 81 ]. Cdc42 inhibition was described to induce hepatic differentiation and maturation in UCMSCs involving CK-18 and other key hepatic genes [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that these spheroids can partially support liver function in hepatectomized animal model after subcutaneous or intraperitoneal transplantation [34]. Similar to iPSCs and ESCs, MSCs also have shown a high hepatic differentiation potential either in vivo or in vitro model [35]. Bone marrow-derived MSCs demonstrated an enhanced expression of hepatocyte-specific markers and exhibited hepatocellular function after introduction to the liver decellularized scaffold in the presence of EGF and HGF ( Fig.…”
Section: Cell Sources For Liver Regenerationmentioning
confidence: 94%